Intervensi Kombinasi Diabetes Self Managemen Education (DSME) Dengan Senam Kaki Diabetik pada Ny.A Dengan DM Tipe 2 : Case Study - Kurniawati, Ayusmia; Tri Rahayu, Henik (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Type 2 diabetes mellitus (DM) is a metabolic disorder caused by pancreatic dysfunction, characterized by hyperglycemia and associated with macrovascular and microvascular complications such as heart disease, stroke, retinopathy, diabetic foot, and neuropathy affecting sensory, motor, and autonomic functions. Effective management of DM requires a comprehensive approach, including non-pharmacological interventions such as diabetic foot exercises and health education through Diabetes Self-Management Education (DSME). To evaluate the effect of combining DSME and diabetic foot exercises on blood glucose levels in patients with type 2 DM. This case study was conducted as part of a community service program in Dusun Cokro, Malang, from April 23 to May 1, 2025, involving one patient with type 2 DM (Mrs. A, 62 years old) who was not undergoing routine treatment. The intervention consisted of 10–20 minutes of education and 20–30 minutes of daily foot exercises for 6 days (3 days supervised and 3 days independent practice). Data were collected through interviews, observation, documentation, and the DKQ-24 questionnaire. Evaluation was performed by measuring blood glucose levels and assessing knowledge before and after the intervention. There was an improvement in the patient’s knowledge and a reduction in blood glucose levels following the intervention. The combination of DSME and diabetic foot exercises is effective in increasing knowledge and lowering blood glucose levels in patients with type 2 DM, and it can be applied within community nursing practice.